Manajemen Risiko Sistem Informasi Perpustakaan (Studi Kasus di Perpustakaan Universitas Riau) - Evi Susanti; Endang Murniati; Nurhayati; Rusmadi Awza (Jurnal Gema Pustakawan, 2021)
In the Unri Library, the risk of information technology (IT) is an event that has the potential to disrupt the service process. IT risks that have not been mapped have resulted in an imbalance in the risk identification process in the Unri Library, so that services are less than optimal. To correct this imbalance, IT risks must be identified and IT services must be improved so that the library service process is not stalled. The purpose of this study was to obtain an overview of the application of the NIST SP 800-30 framework by the Unri Library for risk evaluation of library information systems. The method used in this research is to conduct interviews with people who are directly involved with the Unri Library SLiMS application system. The findings of this study can be used to map risks by detailing how to assess the risk of library information systems and how to manage the dangers of Unri's library information systems.